(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today in the evers swifting world the life is changing towards ubiquitous computing and all human beings are releasing on the fly activity. In the view of this wireless sensor network is playing a key role in every use case. Due to the design issues like distributed nature, decentralized operations WSN is facing prominent security issues like attacks which includes Denial of Service (DoS), Black hole, Gray hole, Flooding and TDMA. This research puts forward a survey of state of the art. Furthermore this research also presents a full proof intrusion prevention framework based on deep learning and findings of the proposed system is also presented in this research with comparison of the state of the art. This paper also discusses the significance of the results and future outlook.